Analisis Rasio Keuangan untuk Penilaian Kinerja Keuangan PT Semen Indonesia (Persero) Tbk - Wahyu Agustin Milasari; Nuryadi Nuryadi (Journal Economic Excellence Ibnu Sina, 2023)
This research aims to analyze financial statements with the ratio techniques at PT Semen Indonesia (Persero) Tbk. period 2020 – 2021. The data studied is in the form of the financial statements of PT Semen Indonesia (Persero) Tbk. period 2020 – 2021. The data collection technique used is a documentation technique. The data analysis technique used is a qualitative descriptive analysis technique. The results of this research are based on the Liquidity Ratio using three formulas namely Current Ratio, Quick Ratio, and Cash Ratio with the company financial performance not good. The Solvency Ratio uses two formulas namely Debt To Asset Ratio and Debt To Equity Ratio with the company financial performance not good. Profitability ratio use three formulas namely Return on Assets and Return on Equity with the company financial performance not good, and Gross Profit Margin with the company financial performance good. Activity ratio use three formulas namely Total Asset Turnover Ratio and Inventory Turnover Ratio with the company financial performance not good, and Receivable Turnover Ratio with the company financial performance good. The benefits of liquidity ratios, solvency ratios, profitability ratios, and activity ratios are to assess the financial performance of the company whether in good condition or otherwise.